Design thinking and imitatio in an educational setting. Issue 3 (3rd July 2017) - Tosca, Susana; Ejsing-Duun, Stine
ABSTRACT: Schools are expected to prepare students for the future, providing them with methods for dealing with the emergent world. This article considers how teachers can work with digital productions at primary schools even when they are not acquainted with the new production genres. We propose a methodological framework to assist students and teachers in their exploration of unknown media genres based on a case study. We revive the ancient concept of imitatio and integrate it with contemporary design thinking to support production dynamics that lead to increased digital literacy.